Particulate Air Pollution from Motor Vehicles: A Putative Proallergic Hazard? - Riccardo Polosa; Sundeep Salvi (Canadian Respiratory Journal)
Air pollution generated from motor vehicle exhaust has become a major cause for scientific and public concern worldwide over recent years. The rapid and marked increase in the motor vehicle traffic and its associated emissions in urban areas have paralleled a sharp increase in the prevalence of allergic diseases such as asthma and rhinitis. Epidemiological studies have demonstrated a strong association between people living in close proximity to roads with high traffic density and increased allergic symptoms, reduced lung function and increased sensitization to common aeroallergens. Several laboratory-based studies have demonstrated that pollutants emitted from motor vehicles can induce allergic inflammation and increase airway hyperresponsiveness, which may provide an underlying mechanism for the increasing prevalence of allergic diseases. Although the detrimental effects of air pollution on human health have been brought to public attention, it appears that less attention has been given to the potential role of road traffic fumes in the induction of the allergic state. Legislators should consider pollutants emitted from motor vehicle exhausts as a potential pro-allergic hazard, before making important changes in environmental policy.